Synthesis and Computational Design of Dual-Targeting Thienopyrimidine Kinase Inhibitors: DFT Guided Optimization of Covalent EGFR/VEGFR2 Inhibition with Favorable Docking and ADMET Properties - Ghafoor, Abdul; Rasool, Javeria; Sajid, Naved; Asghar, Hibba; Ali, Danish; Fatima, Hasba; Shahzaib; Chaudhary, Amina Zara; Abbas, Muhammad Amir; Abid, Amin (European Journal of Applied Sciences, 2025)
In the present study we report the thienopyrimidine kinase inhibitors through integrated computational methods at DFT/B3LYP/6-31++G(d,p). Quantum chemical calculation and molecular docking was employed to explore reactivity and medicinal significance. Evaluation of two derivatives against CDK2, GSK-3β, EGFR T790M, JAK2 V617F-JR-1, and VEGFR2 revealed that VEGFR2-JR-2 exhibited superior binding (-5.625 kcal/mole) via π-cation interactions with TRP531, supported by optimal HOMO localization (98% thienopyrimidine contribution) and favorable quantum descriptors HOMO-LUMO gap = 3.91 eV, electrophilicity = 1.38 eV). DFT-optimized structures identified the optimal warhead position (Fukui = 0.081) for EGFR inhibition. At the same time, GSK-3β-JR-1 demonstrated enhanced hydrophobic complementarity (ΔEvdW = -38.2 kcal/mole with PHE8) correlated with low chemical potential (μ = -3.72 eV). QM simulations confirmed charge transfer 0.32 to kinase hinge regions, and 100 ns MD trajectories validated covalent binding potential (CYS532-S C = 3.4 ± 0.2 Å). These results establish JR-2 as a promising anti-angiogenic lead compound and provide a quantum-validated estimations for developing next-generation thienopyrimidine kinase inhibitors.